Ethanol production from lignocellulosic waste materials: kinetics and optimization studies - Ibrahim, Naeemah A.; Majeed, Halah Hameed; Abid, Rand A.; Alsultan, G. Abdulkareem; Mijan, N. Asikin; Lee, H. V.; Kurniawan, Tonni Agustiono; Taufiq-Yap, Yun Hin (Royal Society of Chemistry, 2025)
This study investigates the composition, hydrolysis, fermentation, kinetic studies and optimization by response surface methodology (RSM) of ten different lignocellulosic materials in ethanol production using enzymatic hydrolysis of isolated Trichoderma reesei and Aspergillus niger and fermentation by Zymomonas mobilis and Saccharomyces cerevisiae. Proximate and ultimate analyses reveal that sugarcane bagasse and rice husk are ideal feedstocks due to their high volatile matter, low moisture, and ash content, offering more fermentable carbohydrates. The highest glucose concentrations were achieved from sugarcane bagasse (0.5689 g L−1) using T. reesei and from rice husk (0.5803 g L−1) using A. niger. Pretreatment increased glucose yields, with rice husk (RHAn) yielding 9.3 g L−1 ethanol in 60 h and sugarcane bagasse (SBTr) yielding 8.1 g L−1 in 48 h, and the particle size reduction to 75 μm enhanced glucose yields due to increased surface area. Kinetic models, including the Monod and Michaelis-Menten models, were used to describe ethanol production, with RHAn exhibiting the highest growth parameters. This study reports optimized ethanol production that achieved maximum yields under controlled conditions, further supporting the feasibility of large-scale bioethanol production.